The Urgency of Considering Age and Psychological Maturity in Applying Indonesian Juvenile Criminal Responsibility System - I Made Agus Astra Wiguna; I Dewa Gede Dana Sugama (Equality : Jurnal Hukum dan Keadilan, 2026)
The determination of criminal responsibility for juvenile offenders remains a complex legal issue, particularly when assessments rely primarily on chronological age without sufficient attention to psychological maturity. Such an approach risks imposing sanctions that are disproportionate to a child’s emotional and cognitive capacity, potentially undermining the rehabilitative purpose of juvenile justice. This study examines how juvenile criminal liability should be determined by integrating both age and psychological maturity within the Indonesian juvenile justice system. Employing a normative juridical method, this research applies statutory and conceptual approaches to analyze relevant legislation, legal doctrines, and theoretical frameworks governing juvenile justice. The findings demonstrate that Indonesia’s juvenile justice system is grounded in the principle of individual accountability, whereby children may be held responsible for criminal acts based on their personal capacity and developmental stage. The system adopts a dual-track sanction model that combines criminal penalties with educational and rehabilitative measures, reflecting an effort to balance accountability with the child’s need for guidance and development. The establishment of a minimum age of criminal responsibility serves as an essential safeguard, preventing children who lack sufficient emotional and cognitive maturity from facing legal consequences they cannot fully comprehend. Ignoring psychological maturity risks distorting the objectives of juvenile justice and may result in negative developmental consequences. Therefore, this study underscores the importance of a holistic assessment that integrates legal age and psychosocial development, supporting a more humane, educational, and rehabilitative approach that enables juvenile offenders to reform, reintegrate, and grow into responsible members of society.